Seismic Wave Propagation and Scattering in the Heterogeneous Earth - Sato, Haruo (Springer, 2017)
Traditionally, acoustics has formed one of the fundamental branches of physics. In the twentieth century, the field has broadened considerably and become increas-ingly interdisciplinary. At the present time, specialists in modern acoustics can be encountered not only in Physics Departments, but also in Electrical and Mechanical Engineering Departments, as well as in Departments of Mathematics, Oceanography, and even Psychology. They work in areas spanning from musical instruments to architecture to problems related to speech perception. Today, six hundred years after Chaucer made his brilliant remark, we recognize that sound and acoustics is a discipline extremely broad in scope, literally covering waves and vibrations in all media at all frequencies and at all intensities.